Actor-Network theory and a methodology for inquiring the online/offline of education - Mörtsell, Sara ; 0000-0002-5079-3067 (Networked Learning Conference 2020, Aalborg, Denmark, 2020-05-18 - 2020-05-20, 2020)
The paper explores what the methodological considerations are for a study of educational practice and networked learning in technologically dense classrooms. The approach of the discussed study is informed by Actor-Network Theory (ANT) (Latour, 2005) and the paper outlines the methodological consequences for adopting principles associated with ANT and post-humanist critiques of representational epistemology. The discussion is organised around overcoming an offline/online binary of educational practice and the use of screen recording software for data collection in ethnographic fieldwork in upper secondary classrooms. In this example, ethical ramifications are brought to the fore in relation to post-humanist traditions (Barad, 2003). The paper argues that the uncertainties exposed by troubling the two categories of human and language, by way of ethno-graphy, can serve as resource for a research practice informed by ANT.